A Systematic Review and Analysis of Palmer Type I Triangular Fibrocartilage Complex Injuries: Outcomes of Treatment - McNamara, Colin T.; Colakoglu, Salih; Iorio, Matthew L. (Journal of Hand and Microsurgery, 2020)
Triangular fibrocartilage complex (TFCC) injuries can present incidentally as an asymptomatic lesion or can cause acute and chronic pain. This study compared different treatment approaches for symptomatic Palmer Type 1 TFCC injuries and rates of improvement using a systematic review of the literature. Two hundred thirty-one articles were identified, 43 met criteria and were included. Two of these articles indicated conservative therapy may be adequate. Patients who underwent debridement for any Type 1 Palmer class returned to work at a rate of 92% (n = 182), but only 44% (n = 38) were free of pain. For 1B lesions that underwent repair, 68.3% (n = 226) were able to return to work and 41% (n = 52) had persistent pain. 1D lesions were treated with both repair and debridement with similar results. Data for Types 1A and 1C were limited as no authors solely addressed these lesions. For 1A lesions, those treated with traditional treatment of debridement still had high rates of being unable to return to work. The literature remains insufficient, making comparison between studies and techniques difficult. For asymptomatic injuries, there is no need for treatment. For patients with recalcitrant symptoms, surgery improves pain, grip strength, and increases return to work and activity. The level of evidence is IV.
Keywords: TFCC; open repair; arthroscopic repair; conservative management; wrist pain